2018
DOI: 10.1038/s41598-018-25343-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate deteriorations and Neanderthal demise in interior Iberia

Abstract: Time and circumstances for the disappearance of Neanderthals and its relationship with the advent of Modern Humans are not yet sufficiently resolved, especially in case of the Iberian Peninsula. Reconstructing palaeoenvironmental conditions during the last glacial period is crucial to clarifying whether climate deteriorations or competition and contacts with Modern Humans played the pivotal role in driving Neanderthals to extinction. A high-resolution loess record from the Upper Tagus Basin in central Spain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 63 publications
2
48
0
5
Order By: Relevance
“…) according to the lithological units described by Wolf et al . (). Furthermore, in order to assess the heavy mineralogical signature of the potential source areas, seven reference samples were taken from the main geological units in the surrounding area that are: (i) Tertiary marls; (ii) metamorphic units and granites from Palaeozoic rocks; and (iii) Mesozoic sedimentary rocks (Fig.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…) according to the lithological units described by Wolf et al . (). Furthermore, in order to assess the heavy mineralogical signature of the potential source areas, seven reference samples were taken from the main geological units in the surrounding area that are: (i) Tertiary marls; (ii) metamorphic units and granites from Palaeozoic rocks; and (iii) Mesozoic sedimentary rocks (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…In higher slope positions, SU‐3 consists of reworked marl material that rests on bedrock (SU‐1, gypsum marl). Optically‐stimulated luminescence (OSL) dating of SU‐3 suggests sedimentation ages beyond 100 ka (Wolf et al ., ). According to a first interpretation, sediments of SU‐3 consist of soil material that was eroded, transported and deposited by a mixture of fluvial and slope processes.…”
Section: Geographic Setting and Background Datamentioning
confidence: 97%
See 2 more Smart Citations
“…A substantial body of marine and terrestrial pollen evidence shows that millennial/centennial-scale instability has been a pervasive feature of the mode of change across southern Europe during glacial periods, with arboreal population size and composition changes associated with sea-surface temperature variations (Sánchez Goñi et al, 2000, 2016aRoucoux et al, 2001Roucoux et al, , 2006Roucoux et al, , 2008Roucoux et al, , 2011Margari et al, 2010Margari et al, , 2014Fletcher et al, 2013). It has been recently suggested that the abandonment of inner Iberian territories by the Neanderthals around 42 ka was caused by deteriorating environmental conditions (Wolf et al, 2018). It is reasonable to assume that similar climatic oscillations occurring during the Middle Pleistocene, would have had a significant impact on hominin populations.…”
Section: Synthesismentioning
confidence: 99%